OPTIMALISASI PENANGKAPAN GAS HASILPEMBUANGAN SAMPAH ORGANIK SEBAGAI SUMBER BAHAN BAKAT ALTERNATIF - Nur Subeki (Jurnal Gamma, 2010)
The research objective is to design a tool catcher gas methane (CH4) and Carbon dioxide gasCO2 in the landfill, as a source of fuel gas.Optimization is a continuation of the initial design of the landfill methane gas capture SupitUrang Malang by Dhieta and Subeki (2007). The optimization of the capture of landfill gas activityis structured as follows: melaukan drilling location landfill Supit Urang with age didasrkan lanfill,installing pipe landfill gas catcher, caught with a plastic measuring, taking samples with timedifferences, measurement and data analysis followed by a discussion.Results obtained from this study include: Age garbage largely determines the capacity of thegas produced is located in cell 4, the other side of the retrieval time also affects the capacity of thecatch during the day.Key words: Optimization,